Antibacterial and antifungal properties of Methanolic Extracts of Some Fleshy Mushrooms of Odisha - Panda, Jiban Jyoti; Gupta, N. (Mushroom Research, 2018)
Twelve different wild and non-edible mushrooms namely-Amanita australis, Amanita vaginata, Conocybe apala, Dacryopinax spathularia, Entoloma incanum, Hirneola auricular, Hygrocybe russocoriace, Leucocoprinus cretatus, Marasmieus anomalus, Marasmieus haematocephalus, Marasmius plicetus and Pluteus lutescens were evaluated for bioactive properties against 4 bacteria and one fungus. Antimicrobial activity was determined by well diffusion method on Nutrient agar and Sabouraud dextrose agar medium by using methanolic extracts of above mushrooms. Most of mushrooms species showed antibacterial activity PPB-1 (gram â€“ve) bacteria. Amanita australis, Conocybe apala and Leucocoprinus cretatus also showed activity against bacteria PPB5 (gram -ve). Most of the mushrooms species studied in the present work exhibited growth inhibition against gram -ve bacteria where as only Amanita vaginata, Conocybe apala, Leucocoprinus cretatus and Marasmieus haematocephalus were found to be active against MLB-6 (gram +ve) bacteria. No growth inhibition of was observed in fungus i.e., Colletotrichum and bacteria PPB-9 (gram -ve) along with no activity was found from the methanolicÂ extracts of Hygrocybe russocoriace against all test organisms. This preliminary screening has opened a line of approach for the mass scale extraction of bioactive compounds which is responsible for the inhibition activity againstÂ bacteria. Keywords:- Methanolic extracts, bioactive compound, antimicrobial activity, mushrooms.